Pengaruh Latihan Tendangan Sasaran Tetap Dan Tendangan Sasaran Berubah Terhadap Ketepatan Tendangan Penalti Pada Siswa SSB Bina Tunas Muda Kabupaten Purworejo - Ikhsani, Laila Qohar; Sudarmono, Martin (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study aimed to determine: (1) the effect of fixed target kicking training on the accuracy of penalty kicks, (2) the effect of changing target kicking training on the accuracy of penalty kicks, and (3) which training method is more effective between fixed target kicking training and changing target kicking training in improving penalty kick accuracy. The population in this study consisted of 20 students of SSB Bina Tunas Muda, Purworejo Regency, who were also used as the research sample. This research employed a quantitative experimental method using a pre-test and post-test group design. The sample was divided into two groups receiving different treatments, namely fixed target kicking training and changing target kicking training. Data analysis was conducted using SPSS with descriptive analysis, normality tests, homogeneity tests, and hypothesis testing using the t-test. The results showed that both training methods significantly improved penalty kick accuracy. The fixed target kicking training group showed an increase from a pre-test mean score of 10.90 to a post-test mean score of 18.00 with an improvement of 65.14%. Meanwhile, the changing target kicking training group improved from a pre-test mean score of 10.90 to a post-test mean score of 17.20 with an improvement of 57.80%. Therefore, fixed target kicking training was found to be more effective than changing target kicking training in improving the penalty kick accuracy of students at SSB Bina Tunas Muda, Purworejo Regency.